DEMITOLOGI BUDAYA JAWA: AKULTURASI TRADISI BAJONG BANYU DALAM MENGEMBANGKAN NILAI PENDIDIKAN ISLAM PADA MASYARAKAT BANJARENEGORO MAGELANG - Nurul Azizah; Kholid Masyhari; Reksiana (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
Javanese people and their culture are very attached to beliefs that are full of mythologizing, sacralization (sacred), and mystification (seeing something as a mystery). The demitology of the Bajong Banyu tradition tries to understand that Javanese culture is not just a myth, but a tradition that is full of the values of Islamic education in it. This research belongs to the type of qualitative field research25 which directly understands the portrait of “Demythology of the Bajong Banyu Tradition in developing the Value of Islamic Education”. Data collection methods used are observation, interviews, and documentation. While the data source is the community. The results of this study indicate that in the Bajong Banyu tradition, Islamic educational values are contained, including social values, religious values, and artistic values. Parents are encouraged to introduce Indonesian cultures as early as possible so that they instill a love for their own culture.